On this side of the fence: Functional responses to linear landscape features shape the home range of large herbivores. Issue 2 (9th December 2021) - Seigle‐Ferrand, Juliette; Marchand, Pascal; Morellet, Nicolas; Gaillard, Jean‐Michel; Hewison, A. J. Mark; Saïd, Sonia; Chaval, Yannick; Santacreu, Hugo; Loison, Anne; Yannic, Glenn; Garel, Mathieu
Abstract: Understanding the consequences of global change for animal movement is a major issue for conservation and management. In particular, habitat fragmentation generates increased densities of linear landscape features that can impede movements. While the influence of these features on animal movements has been intensively investigated, they may also play a key role at broader spatial scales (e.g. the home range scale) as resources, cover from predators/humans, corridors/barriers or landmarks. How space use respond to varying densities of linear features has been mostly overlooked in large herbivores, in contrast to studies done on predators. Focusing on large herbivores should provide additional insights to understand how animals solve the trade‐off between energy acquisition and mortality risk. Here, we investigated the role of anthropogenic (roads and tracks) and natural (ridges, valley bottoms and forest edges) linear features on home range features in five large herbivores. We analysed an extensive GPS monitoring database of 710 individuals across nine populations, ranging from mountain areas mostly divided by natural features to lowlands that were highly fragmented by anthropogenic features. Nearly all of the linear features studied were found at the home range periphery, suggesting that large herbivores primarily use them as landmarks to delimit their home range. In contrast, for mountain species, ridges often occurred in the core range, probably related to their functional role in terms of resources and refuge. When the density of linear features was high, they no longer occurred predominantly at the home range periphery, but instead were found across much of the home range. We suggest that, in highly fragmented landscapes, large herbivores are constrained by the costs of memorising the spatial location of key features, and by the requirement for a minimum area to satisfy their vital needs. These patterns were mostly consistent in both males and females and across species, suggesting that linear features have a preponderant influence on how large herbivores perceive and use the landscape. Abstract : While most behavioural studies have included linear landscape features to assess the effect of fragmentation on animal movement, few of them have considered the role of such features, and of their density, at the home range scale. The authors fill this gap through a comprehensive approach to the role of anthropogenic and natural linear features on the home range establishment of five different species of large herbivores, ranging from preserved mountains to lowlands highly fragmented by anthropogenic features. ©P. Marchand.